Research on Influential Factors of PM2.5 within the Beijing-Tianjin-Hebei Region in China - Jinchao Li; Lin Chen; Yuwei Xiang; Ming Xu (Discrete Dynamics in Nature and Society)
Air pollutant emissions are problematic hazards in China, especially in the Beijing-Tianjin-Hebei region. In this paper, we use fishbone method to set up the influential factor set of PM2.5 qualitatively. Then we use Spearman rank correlation test and panel data regression model to analyze the data of Beijing-Tianjin-Hebei region from 2012 to 2015 quantitatively. The results show that population density, energy consumption per unit area, concrete production per unit area, industrial proportion, transportation volume per unit area, new construction areas per unit area, road construction length per unit area, and coal consumption proportion are all positively correlated with PM2.5. The proportion of electricity consumption is negatively correlated with PM2.5. Among them, population density, industrial proportion, transportation volume, energy consumption per unit area, and the proportion of electricity consumption have a pivotal influence on PM2.5. At last, we give some suggestions to solve the hazard of PM2.5 in Beijing-Tianjin-Hebei region.